Application of Contextual Teaching And Learning Strategies to Improve Biology Learning Understanding on Ecosystem Materials at MAS YPRA Batang Kuis - Indayana Febriani Tanjung; Fatayatul Fikri; Mariska Maudjana Siregar; Hazhiyah Ahsa Sinaga; Zahrafal Hayati (Lembaga Penelitian dan Pengembangan Teknologi dan Rekayasa, Yayasan Ahmar Cendekia Indonesia, 2022)
Contextual learning strategies are applied using technology-based tools to add insight to students by teaching the Ecosystem material described. The purpose of this research is to increase the ambition and achievement of students by implementing contextual learning strategies using technology media tools in the form of learning videos on ecosystem materials in contextual learning. This research was conducted at Madrasah Aliyah, Raudhatul Akmal Batang Kuis Education Foundation by applying contextual learning strategies assisted by learning media in the form of learning videos about ecosystems. Contextual Learning Strategy Teaching Learning helps students understand their level of understanding of ecosystems well. The results of this study indicate that only 5 people in the highest level of understanding category and 8 people in the middle category are included in the lowest level category. By using the teaching-learning contextual learning strategy, it can be seen that there is an increase in the level of understanding in the learning process as many as 34 students.